PENDIDIKAN ISLAM MEMBENTUK NILAI DAN KARAKTER PESERTA DIDIK - Ahmad Ahmad; Sakinah Aljufri (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2019)
Objectives Writing this article to add insight into Islamic Education shapes the values ​​and character of students who will benefit all parties. This study uses a literature study method with data collection techniques utilizing sources / materials from appropriate books and journals. This article attempts to outline the concept of Islamic education to shape the values ​​and character of students discussing Islamic education in the context of Islamic values ​​and education as a character frame and author's approach to argumentation. Islamic education shapes the values ​​and character of students taught values ​​and characters, taught the Koran and Hadith as a guideline for life, taught fiqh as legal signs in worship, taught Islamic history as an example of life, and taught morals as human behavior guidelines whether in good or bad category. Therefore, the main goal of Islamic Education shapes the values ​​and character of students is the formation of personality in students who are reflected in their behavior and mindset in everyday life. Besides that, the success of learning value and character of students in one of the schools is also determined by the application of appropriate learning methods